2019
DOI: 10.1001/jamaophthalmol.2018.4477
|View full text |Cite
|
Sign up to set email alerts
|

Myocilin Gene Gln368Ter Variant Penetrance and Association With Glaucoma in Population-Based and Registry-Based Studies

Abstract: IMPORTANCE The p.Gln368Ter (rs74315329) risk allele in the myocilin gene (MYOC) was initially reported to have high penetrance in glaucoma registry-based studies, but much lower estimates were recently obtained from population-based studies. We investigated this disparity using data from Australia and the United Kingdom. OBJECTIVES To examine the penetrance and effect size of the MYOC p.Gln368Ter variant with glaucoma and ocular hypertension (OHT). DESIGN, SETTING, AND PARTICIPANTS This cross-sectional study w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
47
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 37 publications
(51 citation statements)
references
References 44 publications
3
47
1
Order By: Relevance
“…This magnitude of risk was previously only reported for rarer monogenic variants. 43 Gao et al 44 constructed an inclusive PRS using 1691 SNPs associated with IOP using a more lenient statistical threshold (P < 5 × 10 −5 ) and reported a six-fold higher POAG risk in the top quintile relative to the bottom quintile of an internal validation dataset (OR, 6.34 [95% CI, 4. 82-8.33]).…”
Section: Primary Open Angle Glaucomamentioning
confidence: 99%
See 1 more Smart Citation
“…This magnitude of risk was previously only reported for rarer monogenic variants. 43 Gao et al 44 constructed an inclusive PRS using 1691 SNPs associated with IOP using a more lenient statistical threshold (P < 5 × 10 −5 ) and reported a six-fold higher POAG risk in the top quintile relative to the bottom quintile of an internal validation dataset (OR, 6.34 [95% CI, 4. 82-8.33]).…”
Section: Primary Open Angle Glaucomamentioning
confidence: 99%
“…This magnitude of risk was previously only reported for rarer monogenic variants. 43 Gao et al 44 constructed an inclusive PRS using 1691 SNPs associated with IOP using a more lenient statistical threshold ( P < 5 × 10 −5 ) and reported a six-fold higher POAG risk in the top quintile relative to the bottom quintile of an internal validation dataset (OR, 6.34 [95% CI, 4.82–8.33]). This improved risk prediction can be attributed to a more inclusive SNP selection in the PRS; however, a limitation of this approach was that the test cohort and the GWAS discovery cohort were both from the UK Biobank and thus share geographic, temporal, and methodological properties.…”
Section: Clinical Utility Of the Prs In Ophthalmologymentioning
confidence: 99%
“…10 The most common pathogenic variant in the MYOC gene in individuals of European ancestry (p.Gln368Ter) has a minor allele frequency of 0.13%, yet carries a significant risk of glaucoma with high IOP in those who carry it (in a population based setting odds ratio [OR] = 6.76 with 95% confidence interval [CI] of 4.05-11.29). 11 In family-based studies, the penetrance of p.Gln368Ter to manifest POAG is reported at approximately 80% by the seventh decade of life. 11 IOP in the normal population is a polygenic trait, with recent large genome-wide association studies (GWAS) discovering more than one hundred common loci associated with IOP, accounting for 40% of the heritability.…”
mentioning
confidence: 99%
“…11 In family-based studies, the penetrance of p.Gln368Ter to manifest POAG is reported at approximately 80% by the seventh decade of life. 11 IOP in the normal population is a polygenic trait, with recent large genome-wide association studies (GWAS) discovering more than one hundred common loci associated with IOP, accounting for 40% of the heritability. [12][13][14] Khawaja et al reported that these single nucleotide polymorphisms (SNPs) explained 17% of IOP variance in an independent clinical study, and 9% in the UK biobank study which likely reflects the difference in IOP measurement methods.…”
mentioning
confidence: 99%
“…For the entirety of my candidature, I have also worked on the genetics of other complex traits and outcomes such as addiction, illicit substance use, psychiatric disorders, other malignant cancers and a series of eye-related diseases [156,[339][340][341]. A list of these investigations that were not covered in this thesis was added to Appendix B. I did not expand on any of these projects for several reasons.…”
Section: Application Of Mr In Other Research Areasmentioning
confidence: 99%